2019
DOI: 10.7150/thno.32796
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs negatively regulate cancer stem cells by physically binding FMRP against CCAR1 complex in hepatocellular carcinoma

Abstract: Circular RNA (circRNA) possesses great pre-clinical diagnostic and therapeutic potentials in multiple cancers. It has been reported playing roles in multiple malignant behaviors including proliferation, migration, metastasis and chemoresistance. However, the underlying correlation between circRNAs and cancer stem cells (CSCs) has not been reported yet. Methods: circZKSCAN1 level was detected in HCC tissue microarrays to clarify its prognostic values. Gain and loss function experiments w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
157
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(158 citation statements)
references
References 40 publications
1
157
0
Order By: Relevance
“…CircRHOT1 was found to promote hepatocellular carcinoma (HCC) growth through the recruitment of TIP60 to the promoter of NR2F6 and initiating NR2F6 transcription [49]. A study reported that circZKSCAN1 physically bound an RBP FMRP against CCAR1 complex and inhibited HCC [50]. Circ-Foxo3 was found to bind both cyclin-dependent kinase (CDK) 2 and a known CDK-inhibitor p21.…”
Section: Discussionmentioning
confidence: 99%
“…CircRHOT1 was found to promote hepatocellular carcinoma (HCC) growth through the recruitment of TIP60 to the promoter of NR2F6 and initiating NR2F6 transcription [49]. A study reported that circZKSCAN1 physically bound an RBP FMRP against CCAR1 complex and inhibited HCC [50]. Circ-Foxo3 was found to bind both cyclin-dependent kinase (CDK) 2 and a known CDK-inhibitor p21.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In our study, we identified 12 splicing factors that were abnormally expressed in HCC. Previous studies identified splicing factors associated with HCC, such as PFS, 31 FMRP, 32 YB-1, 33,34 hnRNPH1, 35 and SRp20. 36,37 However, these studies did not perform functional analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Yanjie Wang et al demonstrated that circRNA_ 014511 could affect the expression of P53, regulate cell apoptosis and cell cycle arrest, and influence the radiosensitivity of bone marrow mesenchymal stem cells (BMMCs) by adsorbing miR-29b-2-5p. Furthermore, Yan-Jing Zhu et al found that circZKSCAN1 suppressed cell stemness in HCC by regulating the function of the RBP fragile X mental retardation protein (FMRP), whose downstream target gene is cell cycle and apoptosis regulator 1 (CCAR1) and showed that CCAR1 acts as a coactivator of the Wnt/β-catenin signaling pathway and upregulates cell stemness [134].…”
Section: Other Pathways Related To Circrnasmentioning
confidence: 99%